A feasibility study with process evaluation of a preschool intervention to improve child and family lifestyle behaviours - Lorraine McSweeney; Vera Araújo-Soares; Tim Rapley; Ashley Adamson (BMC, 2017)
Abstract Background Around a fifth of children starting school in England are now overweight/obese. There is a paucity of interventions with the aim of obesity prevention in preschool-age children in the UK. Previous research has demonstrated some positive results in changing specific health behaviours, however, positive trends in overall obesity rates are lacking. Preschool settings may provide valuable opportunities to access children and their families not only for promoting healthy lifestyles, but also to develop and evaluate behaviour-change interventions. Methods This paper presents a cluster randomised feasibility study of a theory based behaviour-change preschool practitioner-led intervention tested in four preschool centres in the North East of England. The primary outcome measures were to test the acceptability and feasibility of the data collection measures and intervention. Secondary measures were collected and reported for extra information. At baseline and post intervention, children's anthropometric, dietary and physical activity measures as well as family 'active' time data were collected. The preschool practitioner-led intervention included family intervention tasks such as 'family goal-setting activities' and 'cooking challenges'. Preschool activities included increasing physical activity and providing activities with the potential to change behaviour with increased knowledge of and acceptance of healthy eating. The process evaluation was an on-going monthly process and was collected in multiple forms such as questionnaires, photographs and verbal feedback. Results 'Gatekeeper' permission and lower-hierarchal adherence were initially a problem for recruitment and methods acceptance. However, at intervention end the preschool teachers and parents stated they found most intervention methods and activities acceptable, and some positive changes in family health behaviours were reported. However, the preschool centres appeared to have difficulties with enforcing everyday school healthy eating policies. Conclusions The findings from the current study may have implications for nursery practitioners, nursery settings, Local Educational Authorities and policy makers, and contributes to the body of literature. However, further work with preschool practitioners is required to determine how personal attitudes and school policy application can be supported to implement successfully such an intervention. Trial registration ISRCTN12345678 (16/02/17) retrospectively registered.